Diagnostic Yield and Accuracy of Different Metabolic Syndrome Criteria in Adult Patients with Epilepsy - Cabral, Lucas Scotta; Cherubini, Pedro Abrahim; de Oliveira, Marina Amaral; Bianchini, Larissa; Torres, Carolina Machado; Bianchin, Marino Muxfeldt (Frontiers in Neurology, 2017)
Introduction Metabolic syndrome is an emergent problem among patients with epilepsy. Here we evaluate and compare the diagnostic yield and accuracy of different metabolic syndrome criteria among adult patients with epilepsy to further explore the best strategy for diagnosis of metabolic syndrome among patients with epilepsy. Materials and Methods Ninety-five epileptic adults from a tertiary epilepsy reference center were prospectively recruited over 22 weeks in a cross-sectional study. Metabolic syndrome was defined according to five international criteria used for the diagnosis of the condition (ATP3, AACE, IDF, AHA/NHLBI and harmonized criteria). Sensitivity, specificity, positive and negative predictive values and area under the ROC curve were estimated for each criterion. Results In our sample, adult patients with epilepsy showed a high prevalence of obesity, hypertension, and diabetes. However, the prevalence of metabolic syndrome was significantly different according to each criterion used, ranging from 33.7%, as defined by AACE, to 49.4%, as defined by the harmonized criteria (p<0.005). IDF criteria showed the highest sensitivity [S = 95.5% (95% CI 84.5-99.4), p<0.05] and AACE criteria showed the lowest sensitivity and negative predictive value [S = 68.2% (95% CI 52.4-81.4), p<0.05; NPV = 75.8% (95% CI 62.3-86.1), p<0.05]. ROC curve for all criteria studied showed that area under curve (AUC) for IDF criterion was 0.966 and it was not different from AUC of harmonized criterion (p=0.092) that was used as reference. On the other hand, the use of the other three criteria for MetS resulted in significantly lower performance, with AUC for AHA/NHLBI=0.920 (p=0.0147), NCEP/ATP3 = 0.898 (p=0.0067), AACE= 0.830 (p=0.00059). Conclusions Our findings suggest that metabolic syndrome might be highly prevalent among adult patients with epilepsy. Despite significant variations in the yield of different criteria, the harmonized definition produced the highest prevalence rates and perhaps should be preferred. Correct evaluation of these patients might improve the rates of detection of metabolic syndrome and foster primary prevention of cardiovascular events in this population.